PENDAMPINGAN WAJIB PAJAK ORANG PRIBADI MELAPORKAN SURAT PEMBERITAHUAN TAHUNAN DENGAN E-FILING - Hendro Lukman; Clarra Kezia; Esperansya Desmonda Woe; Irene Kim Lie (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2023)
ABSTRACT The tax ratio is needed to predict state revenue. Increasing the tax ratio is highly dependent on the compliance of taxpayers who report their taxes. The factor affecting Reporting is the ease of submitting Annual Tax Returns (SPT). The government through the Directorate General of Taxes (DGT) has reformed the SPT reporting system from paper to digital form by creating an e-filing application. E-filing was introduced several years ago, but until 2023 not all taxpayers can use it properly, especially Individual Taxpayers (WPOP). The huge of WPOP and the limited number of tax personnel, then the DGT has formed a Tax Volunteer (RP) to assist (WPOP in reporting SPT. The Universitas Tarumanagara Tax Volunter Team (RP) in 2023 assists the West Jakarta Regional Office DGT assisting WPOP at the Tambora and Taman Sari Primary Tax Service Offices (KPP). The method is carried out face-to-face to the WPOP using a laptop provided by the KPP which before being assigned is equipped with tax knowledge, the technical use of e-filing, and the code of ethics and communication. Debriefing and good cooperation with the Tax Service Office, RP has completed the task well, as evidenced by the assessment of the WPOP served on Attitude, Knowledge and Communication. Effective RP provides benefits and makes DGT's work easier, for students as a place for technical practical training and soft skill development, as well as for institutions as media for promotion. So, RP activities need to be carried out in the coming years. ABSTRAK Rasio pajak diperlukan untuk memprediksi penerimaan negara. Peningkatan rasio pajak sangat tergantung pada kepatuhan wajib pajak yang melaporkan pajaknya. Faktor yang mempengaruhi pelaporan adalah kemudahan penyampaian Surat Pemberitahuan Tahunan (SPT). Pemerintah melalui Direktorat Jenderal Pajak (DJP) telah melakukan reformasi sistem pelaporan SPT dari kertas ke bentuk digital dengan membuat aplikasi e-filing. E-filing sudah diperkenalkan beberapa tahun lalu, namun hingga tahun 2023 belum semua wajib pajak dapat menggunakannya dengan baik, khususnya Wajib Pajak Orang Pribadi (WPOP). Besarnya WPOP dan keterbatasan jumlah pegawai pajak, maka DJP telah membentuk Relawan Pajak (RP) untuk membantu (WPOP dalam melaporkan SPT. Tim Relawan Pajak (RP) Universitas Tarumanagara tahun 2023 membantu Kanwil DJP Jakarta Barat mendampingi WPOP di Kantor Pelayanan Pajak (KPP) Pratama Tambora dan Taman Sari. Metode dilakukan dengan tatap muka WPOP menggunakan laptop yang disediakan KPP yang sebelum ditugaskan dilengkapi dengan pengetahuan perpajakan, teknis penggunaan e -filing, dan kode etik dan komunikasi. Pembekalan dan kerjasama yang baik dengan KPP, RP telah menyelesaikan tugas dengan baik, dibuktikan dengan penilaian WPOP yang bertugas pada Attitude, Knowledge and Communication. Kontribusi kegiatan ini bagi Pekerjaan DJP lebih mudah, bagi mahasiswa sebagai tempat pelatihan praktek teknis dan pengembangan softskill, serta bagi institusi sebagai media promosi, sehingga kegiatan RP perlu dilakukan di tahun-tahun mendatang.